Stepwise Approach to Myopathy in Systemic Disease - Chawla, Jasvinder (Frontiers in Neurology, 2011)
Muscle diseases can constitute a large variety of both acquired and hereditary disorders. Myopathies in systemic disease results from several different disease processes including endocrine, inflammatory, paraneoplastic, infectious, drug and toxin-induced, critical illness myopathy, metabolic and myopathies with other systemic disorders. Patients with systemic myopathies often present acutely or sub acutely. On the other hand, familial myopathies or dystrophies generally present in a chronic fashion with exceptions of metabolic myopathies where symptoms on occasion can be precipitated acutely. Most of the inflammatory myopathies can have a chance association with malignant lesions; the incidence appears to be specifically increased only in patients with dermatomyositis. In dealing with myopathies associated with systemic illnesses, the focus will be on the acquired causes. Management is beyond the scope of this chapter. Prognosis is based upon the underlying cause and, most of the time, carries a good prognosis. In order to approach a patient with suspected myopathy from systemic disease, a stepwise approach is utilized.